Aspects of the Reich's Ministry of Economics. Concept of an Economic Reorganisation of Europe (1940) - Freymond, Jean F. (Studia Historiae Oeconomicae, 1979)
This article investigates the conceptual framework developed by the Reich’s Ministry of Economics (Reichswirtschaftsministerium, RWM) in the summer of 1940 for the economic reorganization of Europe under Nazi Germany’s dominance. The background lies in Germany’s rapid military successes and the expectation of a swift postwar reordering of the continent. With a projected German victory, internal planning bodies began formulating models for Europe’s integration into a German-led economic system. The study focuses on the role of Gustav Schlotterer and the newly formed Abteilung VO (Department for Preparation and Organization), who were tasked with drafting the foundational ideas for this reorganization. Drawing on speeches, policy memos, ministerial correspondence, and archival documents – including statements by Schlotterer and Walther Funk, as well as internal ministry notes – the article reconstructs both the content and evolution of these plans. The analysis identifies three key objectives: (1) ensuring German security through autarky in strategic resources; (2) insulating Europe from economic fluctuations by imposing centralized price and trade control; and (3) granting Germany the ability to direct European production and eliminate economic competition, particularly from the United States, France, and Britain. The RWM envisioned not only state-led economic dominance but also active participation of German businesses in shaping European economies through direct control, influence, and structural integration. Although the concept was never fully implemented and eventually deprioritized, the article argues that the Abteilung VO’s proposals reflect long-standing German economic anxieties and ambitions. They provide valuable insight into Nazi wartime economic planning and the envisioned transformation of Europe into a Reich-centric Grossraumwirtschaft (large economic space). The paper also underlines the instrumental role of business elites in these plans and encourages further research into their legacy within occupation policies.